Um Protocolo Simples e Eficiente para Atualização Consistente de Políticas em Redes Definidas por Software com Controle Distribuído∗ - Mattos, Diogo M. F.; Duarte, Otto Carlos M. B.; Pujolle, Guy (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2017: Anais do XXXV Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2017)
New policies are constantly installed on the network. In Software Defined Networks, the various distributed controllers have to install the new policies consistently for assuring that there is no risks of network experiences transient and unexpected configuration states, which compromise the safety and the operation. In this paper, we propose a consistency protocol for serializing policy updates and for composing policies, avoiding conflicts. The main contributions are three-fold: (i) a consistency protocol for serializing policy updates; (ii) a consensus interface for enabling controllers to agree on the latest version of the network configuration; and (iii) an algorithm to verify that the new policy is an update, a refinement, or if it conflicts with other policies that have already been installed. Through formal verification, we show that the proposed consistency protocol ensures global order for all policy updates and that the proposed algorithm correctly composes all policies. The simulation of the proposal in a real network topology shows that the distributed policy update is per-consistent packet and it has a low overhead of control messages.